Hubungan Sikap Dengan Kesiapsiagaan Tanggap Darurat Kebakaran Penghuni Gedung Di Rektorat Universitas Hasanuddin - Sudarman Sudarman (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: Office buildings that are considered relatively safe, in reality faced with hazard potential such as fire.Methods: The research used an analytic survey design with the cress sectional study approach. It involved 100 samples selected using the purposive sampling technique.Results: The data were analysed statistically with chi-square thest shows that the result for the relationship between attitude and altertness is p=0.032 with α=0.05.Conclusion: There is a relationship between attitude and alertness in terms of fire disaster emergency.